2010
DOI: 10.1534/genetics.110.113878
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Architecture of Grain Yield and Related Traits in Zea maize L. Revealed by Comparing Intermated and Conventional Populations

Abstract: Using advanced intermated populations has been proposed as a way to increase the accuracy of mapping experiments. An F 3 population of 300 lines and an advanced intermated F 3 population of 322 lines, both derived from the same parental maize inbred lines, were jointly evaluated for dry grain yield (DGY), grain moisture (GM), and silking date (SD). Genetic variance for dry grain yield was significantly lower in the intermated population compared to the F 3 population. The confidence interval around a QTL was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 52 publications
(42 reference statements)
3
31
0
Order By: Relevance
“…Both GY and GM are considered to be highly polygenic traits, based on QTL mapping results (Schön et al 2004;Huang et al 2010). Several authors found in simulation studies and for real data sets that GBLUP models were superior to or equally well performing as Bayesian wholegenome regression methods for such traits (Zhong et al 2009;Hayes et al 2010;Clark et al 2011;Kärkkäinen and Sillanpää 2012;Wimmer et al 2013).…”
Section: Comparison Of Prediction Methodsmentioning
confidence: 99%
“…Both GY and GM are considered to be highly polygenic traits, based on QTL mapping results (Schön et al 2004;Huang et al 2010). Several authors found in simulation studies and for real data sets that GBLUP models were superior to or equally well performing as Bayesian wholegenome regression methods for such traits (Zhong et al 2009;Hayes et al 2010;Clark et al 2011;Kärkkäinen and Sillanpää 2012;Wimmer et al 2013).…”
Section: Comparison Of Prediction Methodsmentioning
confidence: 99%
“…This may not necessarily be a disadvantageous feature of MAGIC populations if it allows the identification of QTL with consistent effects over a diverse set of complex backgrounds. It has also been suggested that with the increased number of recombinations, there could be a breakage of small QTL that were previously linked, reducing the ability to detect them (Huang et al 2010). Such an effect has not been seen Using average MAGIC line values (correlation is significant at *P = 0.003 level, which is the Bonferroni corrected level equivalent to P = 0.05; and correlation is significant at the **P = 0.001 level).…”
mentioning
confidence: 99%
“…For example, in a nine-generation advanced intercross used for fine mapping body weight in chickens, BESNIER et al (2011) could only detect five of the nine QTL that were earlier found with the original F2 population. Similar results have been found in advanced crosses of maize (HUANG et al 2010) and mice (WANG et al 2003;LIONIKAS et al 2010).…”
Section: Finer Scale Qtl Localisation and Annotation Of The Qtl-contasupporting
confidence: 87%